Dakwah Nafsiyah dalam Peningkatan Keshalehan Individual Siswa di Masa Pandemi Covid-19 - Heni Ani Nuraeni; Novi Andayani; Afni Rasyid (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2022)
This paper aims to analyze nafsiyah da'wah as a strategy for increasing the individual piety of students at MTs Muhamdiyah Ciputat, South Tangerang. Specifically, this article reveals how to increase individual piety during the COVID-19 pandemic. The research uses a qualitative descriptive method—data obtained through observation and interviews. The results showed increased individual piety regarding reading the Qur'an, prayer skills and istikomahan in carrying out the five daily prayers. The increase in individual piety occurs because of self-awareness of as much as 87 per cent and parental control of as much as 13 per cent. Da'wah nafsiyah, oriented to individual development, is carried out through formal religious teachings, which have implications on the broader scope of life. Consistency in practising the teachings of worship, such as prayer and improving skills in reading the Qur'an become mental exercises that will affect self-control and encourage the formation of good morals.